Satisfação profissional da equipe de enfermagem da Unidade de Terapia Intensiva adulto de um hospital de ensino - Versa, Gelena Lucineia Gomes da Silva (2011)
Quantitative approach, transversal, descriptive and exploratory study, with the overall purpose to investigate the job (In)satisfaction of adult intensive care unit nursing staff of a teaching hospital. The sample was composed of 27 (82%) nurses working in ICU-Adult, which answered through the technique of structured interview the questionnaire Index of Work Satisfaction (IWS) in October 2010. The IWS is consisted of two parts, the first contains 15 items adapted for collection of demographic data and Part II includes two sub-items A and B. In subsection A, they are contained 15 pairs of matched combination of the six components of the IWS (Autonomy, interaction, professional status, job requirements, organizational standards and Compensation). The subsection B composes 44 objective questions with answer options on Likert scale. For the level of job satisfaction, it was worked weighted measurement between sub-item A and B of Part II of the IWS from the multiplication of the weighting of the components (obtained in the calculation of paired comparisons) by the average score of each component (dividing the total score of each component by the number of items of the same). This result provided the adjusted score for each component of job satisfaction. After that, they were added the component scores adjusted and divided by the number of components (06), resulting in IWS. The data were compiled in databases of Microsoft Office Excel ® 2003, and then the information from these spreadsheets were imported to the software Statistica 8.0 ® to analysis for descriptive statistics. The results were presented in the form of three scientific papers. In the first article, they were discoursed the results of the integrative review on the job satisfaction of intensivist nursing staff, in it was obtained a total of 11 (69%) publications which showed dissatisfaction among nursing professionals that correlated to the characteristics of service itself as customer service in a state of extreme gravity, high workload and indoors. In the second article, it was evaluated which components of IWS were considered of greater or lesser importance attributed to job satisfaction and also the perceived satisfaction for each component. The nurses reported greater satisfaction attributed to the remuneration component and the nursing staff interaction. The component of higher perceived satisfaction for both categories was the organizational norms. In contrast, the component that had lower satisfaction awarded, and also perceived satisfaction among nurses and nursing technicians, referred to professional status. In the third article, it was computed the overall IWS and it was evaluated the influence of sociodemographic characteristics on the level of job satisfaction. The IWS was 11,01 among nursing technicians and 8,62 among the nurses. The characteristics: female gender, aged between 20 and 29 years old, presence of children, dual employment, married status, low pay, higher time working in critical unit and the nurse function were effectived in lower levels of job satisfaction. It was concluded from the productions that the intensivist nursing staff was presented dissatisfied at work. The lack of recognition and appreciation of the nursing profession by other professions and/or society is presented as the main factor of dissatisfaction, both in scientific production, as among the respondents in our study (nurses and nursing technicians), because professional status component highlighter as one less job satisfaction.